A Novel Sandwiched Porous MXene/Polyaniline Nanofibers Composite Film for High Capacitance Supercapacitor Electrode. Issue 12 (22nd May 2021) - Chen, Binxia; Song, Quancheng; Zhou, Zehang; Lu, Canhui
Abstract: As a class of promising 2D material, MXenes are widely applied to energy storage systems (ESSs) due to metallic conductivity and high electrochemical activities, but the restacking problem during electrode preparation restricts their electrochemical performances. Herein, polyaniline nanofibers (PANINFs) are used as conductive interlayer spacers to induce the self‐assembly of MXene (Ti3 C2 T x )‐based electrode. The favored sandwiched porous structure is formed due to the electrostatic adsorption and hydrogen bond interaction between the positively charged PANINFs and the negatively charged Ti3 C2 T x nanosheets, which provide abundant accessible sites and facilitate the diffusion of ions. As a result, the flexible freestanding Ti3 C2 T x /PANINFs composite electrode exhibits high conductivity (1373.3 S cm –1 ) and excellent gravimetric capacitance of 645.7 F g –1 . Due to the enhanced structural stability, it achieves impressive cycling stability of 98% capacitance retention after 5000 cycles, which is significantly improved from that of pristine Ti3 C2 T x electrode (84.6%). This work provides a feasible strategy for the structure regulation and performance enhancement of MXene‐based supercapacitors, which has great potential in energy storage systems. Abstract : A facile method is designed to fabricate sandwiched porous MXene (Ti3 C2 T x )/polyaniline nanofibers (PANINFs) composites via a two‐step self‐assembly method. Positively charged PANINFs are used as conductive interlayer spacers for embedding into the negatively charged Ti3 C2 T x layers due to the electrostatic adsorption and hydrogen bond interaction. The composite electrode exhibits excellent structural stability during long‐term cycling.